Characteristic mode analysis of a compact circularly polarized rotated square slot antenna. Issue 6 (16th January 2023) - Oteng Gyasi, Kwame; Boukarkar, Abdelheq; Obeng Kwakye, Kingsford Sarkodie; Ellis, Mubarak Sani; Ahmed, Abdul‐Rahman; Kponyo, Jerry John; Basit, Muhammad Abdul; Shoaib, Nosherwan
Abstract: Presented in this paper is a circularly polarized (CP) wide 45° rotated slot antenna with a broad bandwidth. Characteristic mode analysis is initially carried out to show that, by simply rotating a square slot, CP waves can be radiated if it is properly excited. A simple 50 Ω feedline is then designed to excite the slot for the generation of broadband CP waves. The antenna has a total volume of 30 × 30 × 1.6 mm 3 . Measurement results indicate a broad S11  ≤ −10 dB impedance bandwidth of 85.7% (3.2–8 GHz), a broadband 3 dB axial ratio bandwidth of 57.1% (3.5–6.3 GHz) and a peak gain of 3.6 dBi are obtained by the antenna. The proposed antenna possesses stable radiation patterns as well as relatively flat gain over its operational bandwidth in addition to being compact. It can thus be used for wireless technologies such as WiMAX 3.5 and 5.5 GHz, WLAN 5.2 and 5.8 GHz in addition to Industrial, Scientific, and Medical 5.8 GHz.